Investigation of mycobacterial cell wall genes and their requirement for survival in immune related stressful conditions - Samuels, Veneshley (Department of Clinical Laboratory Sciences, 2021)
Tuberculosis (TB) disease, caused by the pathogen Mycobacterium tuberculosis (Mtb), remains a major global health problem claiming 1.5-2 million lives annually. One of the major factors contributing towards Mtb's success as a pathogen is its unique cell wall and its ability to counteract various arms of the host's immune response. Understanding these survival mechanisms will help us develop new therapeutic interventions that can enhance the capacity of the immune system to kill the pathogen. A recent genome scale study profiled a list of candidate genes that are predicted to be essential for Mtb survival of host mediated responses. One candidate was ftsEX, a protein complex comprised of an ATP binding domain, FtsE, and a transmembrane domain, FtsX. FtsEX functions through interaction with a periplasmic hydrolase, RipC. FtsEX homologs in other bacteria have been linked to a key role in regulation of PG hydrolysis during elongation and division. Using M. smegmatis as a model, we hypothesised that FtsEX and RipC are required in the regulation of PG hydrolysis during normal cell wall elongation and division under stressful conditions in vitro. Antibiotic sensitivity was confirmed using Alamar blue MIC determination assays, which showed that ftsEX and ripC had increased sensitivity to chloramphenicol and not to rifampicin, isoniazid and ethambutol. Our growth curve analysis showed that ftsEX and ripC are not essential for survival in normal growth conditions. However, ftsEX and ripC are conditionally essential for M. smegmatis in low salt media. Growth defects in this condition were characterized by short and bulgy cells, as well as elongated filamentous cells with visible chaining. Major morphological changes were seen under nitrosative stress. A higher proportion of cells struggled to divide normally and formed chains. Lateral branching was also observed in ΔftsE, ΔftsX and ΔftsEX but not in ΔripC. The protein complex was also required for survival in media containing rifampicin. Treatment with the drug exacerbated growth defects of all the mutants, which were much shorter than WT cells, indicating impairment in the elongation process. Collectively, mutants are much shorter in length with an exception of a few extremely lengthy cells, suggesting that ftsEX and ripC are required for both normal cell elongation and division and ultimately for survival in stressful conditions.